Protein–protein interaction map of the Trypanosoma cruzi ribosomal P protein complex - Juri Ayub, Maximiliano (2005)
The large subunit of the eukaryotic ribosome possesses a long and protruding stalk formed by the ribosomal P proteins. Four out of five ribosomal P proteins of Trypanosoma cruzi, TcP0, TcP1alpha, TcP2alpha, and TcP2beta had been previously characterized. Data mining of the T. cruzi genome data base allowed the identification of the fifth member of this protein group, a novel P1 protein, named P1beta. To gain insight into the assembly of the stalk, a yeast two-hybrid based protein interaction map was generated. A parasite specific profile of interactions amongst the ribosomal P proteins of T. cruzi was evident. The TcP0 protein was able to interact with all both P1 and both P2 proteins. Moreover, the interactions between P2beta with P1alpha as well as with P2alpha were detected, as well as the ability of TcP2beta to homodimerize. A quantitative evaluation of the interactions established that the strongest interacting pair was TcP0-TcP1beta.